Pengaruh Kegiatan Ekstrakulikuler Keagamaan Terhadap Pemahaman Siswa Tentang Pendidikan Agama Islam SMP N 1 Padangratu - Suci Erfina Ilianti; M. Latif Nawawi (Al-Bustan: Jurnal Pendidikan Islam, 2024)
Schools often organize non-formal activities to enhance students' understanding of Islamic religious education, which often receives limited time in the classroom. This underscores the need for greater attention to religious education, as it is an integral part of the school curriculum. This research aims to evaluate the impact of extracurricular religious activities on students' understanding of Islamic Religious Education at SMP N 1 Padangratu Lampung Tengah. The method employed in this study is quantitative, utilizing data collection methods such as Observation, Documentation, and Questionnaires. Data analysis involves summarizing, presenting, drawing conclusions, and verifying data validity. The research findings indicate a significant correlation between extracurricular activities and the improvement of students' understanding of PAI, with an "r" value of 0.418, considered quite strong in the interpretation category.